2020
DOI: 10.1177/1460458220926894
|View full text |Cite
|
Sign up to set email alerts
|

Survey on virtual coaching for older adults

Abstract: Virtual coaching has emerged as a promising solution to extend independent living for older adults. A virtual coach system is an always-attentive personalized system that continuously monitors user’s activity and surroundings and delivers interventions – that is, intentional messages – in the appropriate moment. This article presents a survey of different approaches in virtual coaching for older adults, from the less technically supported tools to the latest developments and future avenues for research. It foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…This is also the case for the study by Gordienko et al (2017) [ 8 ], which also focused on the same aspects, but they are far from Siewiorek’s vision about what a VCS constitutes. In a recent survey, Lete et al (2020) [ 9 ] also found limited technological development on virtual coaching for older adults. More recently, thanks to several research projects funded in 2017 by the European Research and Innovation Action (RIA) on virtual coaching for older adults, more technologically sophisticated systems have started to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…This is also the case for the study by Gordienko et al (2017) [ 8 ], which also focused on the same aspects, but they are far from Siewiorek’s vision about what a VCS constitutes. In a recent survey, Lete et al (2020) [ 9 ] also found limited technological development on virtual coaching for older adults. More recently, thanks to several research projects funded in 2017 by the European Research and Innovation Action (RIA) on virtual coaching for older adults, more technologically sophisticated systems have started to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…While coaching as a face-to-face conversation is the traditional and arguably most common format, virtual coaching refers to remote coaching in a broader sense and coaching conducted by autonomous systems in a narrow sense. Predominantly driven by progress in the field of AI, there is a clear trend towards the last type of coaching (Tropea et al 2019 ; Lete et al 2020 ; Graßmann and Schermuly 2021 ). Nevertheless, combining face-to-face coaching with remote or autonomous coaching in an alternating way is still conceivable and referred to by Geissler et al ( 2014 ) as “Blended coaching”.…”
Section: Conceptual Foundationsmentioning
confidence: 99%
“…Nevertheless, combining face-to-face coaching with remote or autonomous coaching in an alternating way is still conceivable and referred to by Geissler et al ( 2014 ) as “Blended coaching”. The different types can be enriched further with data gathered by digital devices which are placed on the user’s body (also called wearables), in the user’s environment (e.g., smart objects), or sensed data stored in databases (e.g., weather data) (Lete et al 2020 ). We call this data enrichment of the coaching process that enables a high degree of context-awareness “digital ubiquity”.…”
Section: Conceptual Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAAM coaching system is a coaching system mainly targeted at the elderly that aims to support its users to continue living independently and comfortably for as long as possible. In contrast to typical AAL coaching approaches [21], it does not exclusively rely on directly delivering the coaching messages to users, but primarily focuses on delivering it to their social circles: family, friends, neighbors, and organized caregivers.…”
Section: The Saam Coaching Systemmentioning
confidence: 99%